Pengaruh Variasi Suhu Air 27ºC, 37ºC, 47ºC Pada Campuran Beton Terhadap Nilai Kuat Tekan Beton Struktural - Fatma Rosita Hardiani; Mirza Ghulam Rifqi; Mohamad Galuh Khomari (Journal of Applied Civil Engineering and Infrastructure Technology, 2020)
The purpose of this research was to determine the effect of water temperature on the concrete mixture using water with a temperature of 27ºC, 37ºC, 47ºC in the concrete mixture to value structural concrete compressive strength. This research uses cylindrical specimens with a size of 150 mm diameter and 300 mm in height. The study involved testing compressive strength at the age of 3 days, 7 days, 14 days, and 28 days. Based on the test results, the compressive strength values obtained at 3 days of age with a water temperature of 27ºC to 14.132 MPa, 37ºC to 19.496 MPa, 47ºC to 21.554 MPa. The results of testing at the age of 7 days obtained compressive strength with a water temperature of 27ºC to 19.817 MPa, at 37ºC to 22.471 MPa, at 47ºC to 25.822 MPa. The results of testing at the age of 14 days with a water temperature of 27ºC to 27.090 MPa, at 37ºC to 28.556 MPa, at 47ºC to 28.973 MPa. The results of the test at 28 days the compressive strength of concrete with a water temperature of 27ºC to 30.246, 37ºC to 31.250 MPa, 47ºC to 32.149 MPa. The normal water temperature of 27ºC is used as a reference to see the effect on the value of concrete compressive strength. Based on this study, the use of water in concrete mixtures with temperatures of 37ºC and 45ºC affects the compressive strength of concrete.